Analisis Faktor-Faktor Yang Mempengaruhi Preferensi Konsumsi Pinang Kering di Kecamatan Biboki Anleu Kabupaten Timor Tengah Utara - Painenon, Cindylusi N. A.; Nubatonis, Agustinus; Joka, Umbu (Musamus University, 2024)
In Eastern Indonesia, particularly on the island of Timor, areca nuts are frequently utilized for a variety of customary reasons, including weddings and other occasions connected to local culture and customs. The purpose of this study is to ascertain people's preferences for dried areca nut consumption in the Biboki Anleu District in North Central Timor. The experimental method is the one that is employed. Both primary data and secondary data were gathered for this study. Logistic Regression Analysis is the technique used for data analysis. The study's findings indicate that age, gender, eating habits, flavor, and texture are the aspects of areca nut consumption that influence customer preferences. In the Biboki Anleu District, there are two variables out of the five that affect consumers' preferences for dried areca nuts, specifically taste and texture factors. These results demonstrate the preference for dry areca nuts with a firm texture among customers in the Biboki Anleu district. In other words, these two factors influence the propensity for eating dried areca nuts in the Biboki Anleu District to some extent.